2019
DOI: 10.1007/s00784-019-02935-8
|View full text |Cite
|
Sign up to set email alerts
|

CSF-1 and IL-34 levels in peri-implant crevicular fluid and saliva from patients having peri-implant diseases

Abstract: Objective Colony-stimulating factor (CSF)-1 and interleukin (IL)-34 are growth factors that regulate myeloid cell functions and support osteoclastogenesis. CSF-1 and IL-34 levels in peri-implant diseases are yet unknown. This study evaluated CSF-1, IL-34, and IL-1β levels in saliva and peri-implant crevicular fluid (PICF) from patients having mucositis or peri-implantitis, as well as their correlation to clinical parameters of disease. Material and methods Forty-three patients were included (mean age 61.1 ± 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…Increased tissue expression of CSF‐1R has also been reported in several forms of cancers, 26 and in other inflammatory diseases such as RA and IBD 10,27 . Our results on CSF‐1R expression in PD gingival tissue is interesting given that we have reported elevated levels of CSF‐1 in gingival tissue and saliva from PD patients, 13,14 and in peri‐implantitis crevicular fluid 28 . Furthermore, gingival fibroblasts enhance their CSF‐1 secretion after pro‐inflammatory stimulation in vitro 13 …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Increased tissue expression of CSF‐1R has also been reported in several forms of cancers, 26 and in other inflammatory diseases such as RA and IBD 10,27 . Our results on CSF‐1R expression in PD gingival tissue is interesting given that we have reported elevated levels of CSF‐1 in gingival tissue and saliva from PD patients, 13,14 and in peri‐implantitis crevicular fluid 28 . Furthermore, gingival fibroblasts enhance their CSF‐1 secretion after pro‐inflammatory stimulation in vitro 13 …”
Section: Discussionsupporting
confidence: 66%
“…10,27 Our results on CSF-1R expression in PD gingival tissue is interesting given that we have reported elevated levels of CSF-1 in gingival tissue and saliva from PD patients, 13,14 and in peri-implantitis crevicular fluid. 28 Furthermore, gingival fibroblasts enhance their CSF-1 secretion after pro-inflammatory stimulation in vitro. 13 Taken together, these findings imply that the CSF-1/CSF-1R system is involved in the inflammatory processes in PD.…”
Section: Discussionmentioning
confidence: 99%
“…we believe with our study to be the first to show no difference in G-CSF between healthy and diseased implants. Considering that a recent study, which focused on a close relative of G-CSF (i.e., macrophage-CSF) in the PICF of peri-implantitis patients, found higher levels of macrophage-CSF when compared to peri-implant mucositis patients (Lira-Junior et al, 2020), interpretation of our outcomes should be done cautiously. However, one might suggest that colony stimulating factors might play a role in the pathogenesis of peri-implant disease.…”
Section: Healthy Versus Diseased Biomarker Levels In Picfmentioning
confidence: 86%
“…Studies [10,11] have shown that patients with existing or with a history of periodontitis are more susceptible to peri-implant diseases compared with individuals with a healthy periodontal status. Unstimulated whole saliva (UWS) is a biologic oral fluid that expresses raised levels of destructive inflammatory cytokines among patients with periodontal and peri-implant diseases [12][13][14][15][16]. Alpha-amylase (AA) protein represents the autonomic nervous system and contributes towards maintenance of mucosal immunity by inhibiting bacterial colonization, reproduction and adhesion [17,18].…”
Section: Introductionmentioning
confidence: 99%